Ethical decision making of Malaysian external auditors / Razana Juhaida Johari - Johari, Razana Juhaida (Institute of Graduate Studies, UiTM, 2013)
Numerous incidences of unethical behaviours of auditors being reported globally have marked significant dishonours to the auditing profession. The incidences of audit failures have brought the issues of auditors’ ethical decision making quality and independence to the forefront and closely scrutinized. In auditing profession, the ethical decision making is a complex process due to the auditors’ fiduciary obligation to their audit clients and public. The requirements to meet the expectations of these two parties serve as the point where the auditors’ conflicts could arise thus providing threats to auditors’ independence. Despite increased attention from practitioners and scholars in enhancing the ethical values within the auditing profession, the incidences of some wrongdoings involving the auditors stand as evidences that they are continuously making questionable professional judgments that have ethical overtones. A few studies conducted on the auditors’ ethical decision making provides a limited of ethical decision making models to explain certain effect of antecedent factors on the auditors’ ethical behaviour.Hence, based on the social cognitive theory (Bandura, 1986); Rest Theory (1986) and Jones (1991) Model, this thesis addresses this shortcoming by taking into account the combination effect of individual, professional environment and contextual factors on the auditors’ ethical decision making…